THE IMPACT OF ARTIFICIAL INTELLIGENCE ON FINANCIAL ACCOUNTING - Toshtemirov Shoxabbos Komil o’g’li (New modern researchers: modern proposals and solutions, 2025)
In today’s fast-pased world, ”Artificial Intelligence” (AI) is revolutionizing financial accounting by improving efficiency , accuracy, fraud detection, and transparency. This article examines the role of AI in automating financial accounting processes, reducing human error, and improving financial decision-making. Using a number of ways including, a qualitative approach, this article reviews existing literature and case studies on AI-driven accounting software. The findings show that AI significantly reduces manual workload and enhances predictive analytics. Additionally, using AI in financial accounting saves a lot of time , thereby boosting overall economy. However, challenges such as data security risks and job displacement must be addressed.